Impact of Educational Program on Self-Care Among Elderly with Chronic Illnesses at Geriatric Homes - Abbas, Nour Fadhel; Bahlol Naji, Arkan (Journal of Neonatal Surgery, 2025)
Objectives: To determine the Impact of the Education Program on Self-Care by Older Adults with Chronic Diseases. Background: programs aimed at promoting self-care have become a key strategy in empowering older adults to take control of their health. These programs are typically designed to provide individuals with the knowledge and skills necessary to manage their chronic diseases more effectively. Methods: quasi- experimental design, pre-tests and post-tests, with participants of non-probability Purposive sample consists of (30) elderly’s, these subject one group (study). The study is carried out at geriatric homes in Baghdad City. Results: The educational program significantly improved the elderly’s self-care practice behaviors. The overall scores for self-care practice behavior increased significantly from pretest (M = 58.53, SD = 5.758) to posttest I (M = 79.60, SD = 7.356) and posttest II (M = 78.83, SD = 6.983), with a highly significant effect observed by Greenhouse-Geisser correction (F= 139.343, p = .000, Partial Eta Squared = .828). This indicates a strong and significant impact of the education program on enhancing elderly’s self-care practices behaviors. Conclusions: the effectiveness of education programs on self-care for older adults in geriatric homes is crucial for improving the health and well-being of this vulnerable population